Delirium: respuestas pendientes - Martínez F., Gabriel (Revista Hospital Clínico Universidad de Chile, 2008)
The delirium is pathology not reported almost always, that is to say, that does not become the diagnosis, in spite of their high prevalence and incidence, particularly in the intrahospitalary scope, in the services of medicine, the surgical ones and of critical patients. It consists of a state that affects the global cognitive operation, the conscience state, the conduct, the attention, the psychomotor activity, that can oscillate during the day, but that is transitory, unlike the dementia. The few national studies on the subject agree with the international series on the relevance of the delirium, and that its understanding and understanding is in the heat of development like its relation with the dementia, the roll of the depletion of colinergics markers in its physiopathology, etc. It is important to become aware that its diagnosis must be known by all the members of the equipment of health that take care of patients with delirium or risk of developing it, and that, in addition to pharmacological interventions, is had cost-effective preventive measures, of easy application, saving capital a social and financial cost.